Voice over IP in Wireless Heterogeneous Networks Signalling, Mobility, and Security - Fathi, Hanane; Chakraborty, Shyam S.; Prasad, Ramjee; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
The convergence of different types of traffic has preceded the convergence of systems and services in a wireless heterogeneous network. Voice and data traffic are usually treated separately in both 2G and 2.5G wireless networks. With advances in packet switching technology and especially with the deployment of wireless heterogeneous systems, both speech and data traffic are carried over wireless links by the same IP-based packet-switched infrastructure. However, this combination faces some challenges due to the inherent properties of the wireless network. The requirements for good quality VoIP communications are difficult to achieve in a time-varying environment due to channel errors and traffic congestion and across different systems. The provision of VoIP in wireless heterogeneous networks requires a set of time-efficient control mechanisms to support a VoIP session with acceptable quality. The focus of Voice over IP in Wireless Heterogeneous Networks is on mechanisms that affect the VoIP user satisfaction while not explicitly involved in the media session. This relates to the extra delays introduced by the security and the signaling protocols used to set up an authorized VoIP session and to the disruption caused by the user mobility during the session. Voice over IP in Wireless Heterogeneous Networks thus investigates and proposes cross-layer techniques for realizing time-efficient control mechanisms for VoIP: signaling, mobility and security.
IP-Based Wireless Heterogeneous Networks -- Voice over Internet Protocol -- Models for Performance Analysis in Wireless Networks -- Impact of Security on Real-Time Services: Link Layer Authentication Delay in WLAN 802.11b -- Impact of Signalling on Real-Time Services: SIP Session Setup Delay -- Impact of Mobility on Real-Time Services: Handover Delay -- Coupling Mobility and Security -- Towards Quality of Experience and Future Perspectives.
Keywords: ENGINEERING; COMPUTER NETWORK ARCHITECTURES; TELECOMMUNICATION; ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS